Anaplastic lymphoma kinase positive large B‐cell lymphoma: Literature review and report of an endoscopic fine needle aspiration case with tigroid backgrounds mimicking seminoma. Issue 2 (30th September 2016) - Sakr, Hany; Cruise, Michael; Chahal, Prabhleen; Cotta, Claudiu; Cook, James; Chalikonda, Sricharan; Rosenblatt, Steven; Hamadeh, Fatima; Al‐Nourhji, Omar; Sturgis, Charles D.
Abstract : Anaplastic lymphoma kinase‐positive large B‐cell lymphoma (ALK+ LBCL) is a rare distinct type of non‐Hodgkin's lymphoma that arises in association with alterations of the ALK gene. This distinct disease entity is typically associated with an aggressive clinical course and appears in light microscopic preparations as a monomorphic population of large, immunoblast‐like cells. In this report, we describe a case of ALK+ LBCL diagnosed by transgastric endoscopic ultrasound‐guided fine needle aspiration (EUS FNA) of splenic hilar lymph nodes. Modified Giemsa stained direct smears from the FNA sample demonstrated large lesional cells with foamy cytoplasm and macronucleoli admixed with small lymphocytes in tigroid backgrounds, mimicking the cytologic appearance of seminoma. Ancillary immunohistochemical studies subsequently confirmed the diagnosis of ALK+ LBCL with the lesional cells being immunoreactive for CD138, VS38c, MUM1, ALK1, and lambda light chain. The cohesiveness of the cells, the cellular morphology, and the tigroid backgrounds were all pitfalls for accurate diagnosis of this rare specific type of lymphoid malignancy by cytology. To our knowledge this is the first case report detailing the diagnosis of ALK+ LBCL by EUS FNA and the first report describing a glycogen‐rich tigroid background in direct FNA smears. Establishing a refined diagnosis in cases of this rare form of LBCL is necessary, as therapies targeting ALK may be of value in clinical management. Diagn. Cytopathol. 2017;45:148–155. © 2016 Wiley Periodicals, Inc.